2016
DOI: 10.1371/journal.pone.0156237
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Epidemiology and Clinical Impact of Acinetobacter calcoaceticus-baumannii Complex in a Belgian Burn Wound Center

Abstract: Multidrug resistant Acinetobacter baumannii and its closely related species A. pittii and A. nosocomialis, all members of the Acinetobacter calcoaceticus-baumannii (Acb) complex, are a major cause of hospital acquired infection. In the burn wound center of the Queen Astrid military hospital in Brussels, 48 patients were colonized or infected with Acb complex over a 52-month period. We report the molecular epidemiology of these organisms, their clinical impact and infection control measures taken. A representat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 93 publications
0
39
0
Order By: Relevance
“… 104 , 116 , 117 Colistin, an old antibiotic discontinued because of its nephrotoxicity, has re-emerged as an useful agent in the treatment of infections caused by MDRO. 118 , 119 However, due to the use of colistin, the appearance of colistin-resistant organisms is worrisome, as available therapeutic options seem scarce; some studies have reported the usefulness of combination therapy (eg, colistin, amikacin, tigecycline) in the treatment of colistin-resistant infections. 120 , 121 Early consultation of infectious diseases specialists is advocated in challenging cases.…”
Section: Management Of Sepsis In Burn Patientsmentioning
confidence: 99%
“… 104 , 116 , 117 Colistin, an old antibiotic discontinued because of its nephrotoxicity, has re-emerged as an useful agent in the treatment of infections caused by MDRO. 118 , 119 However, due to the use of colistin, the appearance of colistin-resistant organisms is worrisome, as available therapeutic options seem scarce; some studies have reported the usefulness of combination therapy (eg, colistin, amikacin, tigecycline) in the treatment of colistin-resistant infections. 120 , 121 Early consultation of infectious diseases specialists is advocated in challenging cases.…”
Section: Management Of Sepsis In Burn Patientsmentioning
confidence: 99%
“…Due to their capacity for long-term survival in the hospital environment, combined with a formidable inherent and acquired antibiotic resistance, some A . baumannii strains have emerged as important nosocomial pathogens, especially in critically ill patients, as found in intensive care units and burn wound centers [ 3 ]. Multidrug resistant strains of A .…”
Section: Introductionmentioning
confidence: 99%
“…Although it is possible that the different Acinetobacter ASVs that were found in this study resulted from different 16S rRNA sequences being present in a single organism, Acinetobacter is not known to contain different 16S-or we would observe the same results at all concentrations where the genus is present. Such findings are especially important, since the genus is highly recombinogenic [35] and contains various antibiotic-resistant species pathogenic to humans or other organisms, even though we cannot confirm the pathogenicity of the bacterium while using current methodologies [44,45].…”
Section: Discussionmentioning
confidence: 92%